중소도시와 농촌 청소년의 위험행동 영향요인 비교 연구 - 박현숙; 여현주; 정선영; Park, Hyun Sook; Yeo, Hyun Ju; Jung, Sun Young (韓國學校保健學會誌, 2016)
Purpose: This study was to compare and to examine the factors related to risk behaviors of adolescents living in small and medium-sized cities and in rural areas. Methods: The subjects were 545 adolescents (295 from small and medium-sized cities and 250 from rural areas). The data was analyzed by descriptive statistics, Pearson corelation coefficients, and multiple regression with IBM SPSS 19.0 program. Results: The factors influencing the risk behaviors of adolescents in small- medium cities were school, peer risk factors and community risk factors, self- control among protective factors, positive communication with parents, positive peer associations, these variables explained 42.0%. The most important variable explaining the risk behaviors of adolescents in small- medium cities was positive communication with parents, followed by community risk factors, peer risk factors, positive peer relationships, school and self-control. The factors affecting the risk behaviors of rural adolescents were school, personal risk factor, peer risk factor, self- control factor, which explained 38.5% of the risk behaviors of adolescents in rural areas. Among them, the most important variable explaining risk behaviors was personal risk factors, followed by peer risk factors, school, and self-control. Conclusion: These finding suggest a need to develop a strategy to improve positive communication with parents for adolescents living in small- medium cities and a strategy to reduce personal risk factors and peer risk factors for rural adolescents.